2021
DOI: 10.3390/ijms22179505
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable High-Throughput Screening Model for Antidepressant

Abstract: Depression is the most frequent affective disorder and is the leading cause of disability worldwide. In order to screen antidepressants and explore molecular mechanisms, a variety of animal models were used in experiments, but there is no reliable high-throughput screening method. Zebrafish is a common model organism for mental illness such as depression. In our research, we established chronic unpredictable mild stress (CUMS) models in C57BL/6 mice and zebrafish; the similarities in behavior and pathology sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Among them, lisdexamfetamine is a common and classical depression-inducing drug . Zebrafish is highly sensitive to psychotropic drugs and has become a model species for research in neuroscience fields including depression in recent years, which provides an important perspective for depression drug screening …”
Section: Resultsmentioning
confidence: 99%
“…Among them, lisdexamfetamine is a common and classical depression-inducing drug . Zebrafish is highly sensitive to psychotropic drugs and has become a model species for research in neuroscience fields including depression in recent years, which provides an important perspective for depression drug screening …”
Section: Resultsmentioning
confidence: 99%
“…Most of the records sought for inclusion in either stage of screening were excluded because they did not meet the criteria set for the intervention ( n = 89), followed by the population of interest ( n = 42), and the design of the study ( n = 37). Three studies were excluded from the quantitative analyses because the minimum number of studies to perform a meta-analysis was not reached for the outcomes reported (Zimmermann et al ., 2016; Jayamurali & Govindarajulu, 2017; Marcon et al ., 2018), and four studies were excluded because of missing information (Huang, Butler & Lubin, 2019; Zhang et al ., 2021; Kirsten et al ., 2021; Demin et al ., 2021). This resulted in 31 studies included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The open-field test (OFT), forced swimming test (FST), and tail suspension test (TST) were carried out as previously described [ 31 , 49 ]. The OFT was used to observe the behavioral changes in each group of mice and to test the spontaneous activity of the mice.…”
Section: Methodsmentioning
confidence: 99%